PROBLEMATIKA PEMBANGUNAN KARAKTER DAN SOLUSINYA - Fatma Raudhah (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2017)
In character building there are several problems, including the waning of nationalism and national identity, the decline of national dignity and dignity, poor national mentality, multidimential crisis, and the degradation of the moral destroyer of the nation. The character building solution is to increase nationalism and national awareness, the application of character education in Islamic Education, the use of methods of character education in Islamic Education. The methods used are: tarbiyah method, ta'dîb method, tazkiyah method, and tadlrîb (practice) method.